A Flexible Load Flow Algorithm with Network Topology Reconfiguration for Radial and Meshed Distribution Systems Based on Power Summation Approach - Yassine MALIARI; Ahmed ABBOU (Communications of International Proceedings, 2020)
This paper presents a load flow algorithm based on power summation principle, for meshed and radial low and medium voltage distribution networks, based on adaptation of the power summation approach for an on-line use, flexible with network topology reconfiguration. The proposed load flow analysis is based on the use of only linear formulation, based on power summation principle, the proposed load flow algorithm is easy to implement for passive and active distribution networks.
Keywords: Meshed distribution system; Radial distribution system; Load Flow; Power flow summation; Distributed generation; Voltage control; renewable energy.